(untitled) - Maheshwari, Ramesh; Naroliya, Aashish (Asian Journal of Medical Research, 2019)
Background: To understand the effect of small dose clonidine with 0.75% ropivacaine for foot surgery, Hallux valgus repair is a minor surgical procedure, which leads to severe pain post surgicaly. For this reason, regional anaesthesia along with long-acting local anaesthetics has been advised. Subjects and Methods: All patients were screened for any other systemic disorder. Any patients with diabetes, hypertension or thyroid issues were also not included in the study. Patients of age group 18-75 were included in the surgery. The patients were divided randomly into two groups. Group A patients (16 patients) were injected with 1 ?g/kg clonidine to 0.75% ropivacaine during combined sciatic-femoral nerve block for the repair of hallux valgus, whereas group B patients (16 patients) were injected with only 0.75% ropivacaine during the repair procedure. Results: It was observed that, not much difference was seen in the time required to achieve surgical anaesthesia between the patients receiving only 0.75% ropivacaine which was 10 minutes approx. Conclusion: As a result of this prospective, randomized, double-blinded study demonstrate that adding 1 ?g/kg clonidine to 0.75% ropivacaine has no major effect on onset time and quality of combined sciatic-femoral nerve block.